The effectiveness of the method of stabilizing segment C1-C2 Harms in fractures of the odontoid process of C2 vertebra type II - Valeriy Olkhov; Kostyantyn Gorbatyuk; Oleksandr Lemeshov (Ukrainian Neurosurgical Journal, 2015)
Objective. To determine the effectiveness of C2 dens fracture stabilization using Harms method, and to assess the quality of life of patients in the early and late postoperative period.Materials and methods. Analyzed 11 cases of C2 dens fractures type II, which were operated in the Department of Neurosurgery Vinnytsia Regional Psychoneurological Hospital for the period 2012-2014. All operation were made using Harms method.Results. Efficacy was estimated via using the VAS score and the NDI before, 1 and 6 months after surgery. Moreover we performed CT before, 1-2 day after, and 6 month after the operation.Before surgery NDI in average was 46%, first days after the operation  median - 28%. One month later, the median value of NDI is 19%. After 6 months and future NDI is not greatly changed (average 15%).VAS before operation was 6.2. First days after operation  median score was 6.  This score was being reduced to 2.2 after one month and progressively to 0.33 after 6 months.CT performing first days after operation were needed  to confirm right positioning of screws. 6 months after the operation CT were been done to all patients. It showed good bone healing in fracture line.Conclusions. Harms method of C1-C2 stabilization is an effective method for surgical treatment of C2 II type fracture. Over 6 months after operation patients returns to their usual activity without pain.